A composite Fe–C/layered double oxides (Fe–C/LDO) carrier fabrication and application for enhanced removal of nitrate and phosphate from polluted water with a low carbon/nitrogen ratio. (10th June 2022) - Chen, Liang; Quan, Xiangchun; Gao, Zhiqi; Kong, Zhiyuan
Abstract: In this study, a multifunctional biofilm carrier (Fe–C/LDO) integrating Fe–C micro-electrolysis with Mg–Al layered double oxides (LDO) was developed and applied in a biofilter aimed to remove nitrogen and phosphorus simultaneously from slightly polluted water with a low carbon/nitrogen (C/N) ratio. Four types of carriers were prepared under different conditions and their performance in nitrate reduction and phosphorus removal were compared. Results showed that the composite Fe–C/LDO carrier prepared with polyethylene glycol as the pore-forming agent demonstrated the highest nitrate reduction rate and phosphorate adsorption capacity (2.09 mg PO4 3 - -P·g −1 ). A biofilter packed with the Fe–C/LDO carrier was investigated under heterotrophic conditions (C/N = 4.13) and complete autotrophic conditions (C/N = 0) during a long-term operation. Good removal of NH4 + -N (96–98%), TN (92–96%) and PO4 3- -P (50–58%) were achieved in the biofilter under both heterotrophic and autotrophic conditions. High throughput pyrosequencing analysis revealed that a large population of autotrophic denitrifying bacteria Thiobacillus and Thioalkalispira were enriched in the biofilm. Metagenomic analysis was performed to analyze functional genes related to nitrogen metabolism and carbon cycle, and it confirmed the presence of a whole denitrification and Calvin-Benson-Bassham carbon fixation pathway in biofilm. Finally, the possible mechanisms for nitrogen and phosphorus removal in the biofilter were proposed. The Fe–C/LDO carrier not only enriched abundant autotrophic denitrifying bacteria, but also provided numerous Fe–C galvanic cells for nitrate reduction through micro-electrolysis. In addition, the Mg–Al LDO in combination with iron hydroxides generated during micro-electrolysis may contribute greatly to phosphorus removal. Biofilter packed with the multifunctional Fe–C/LDO carrier could be a promising technology for simultaneous nitrogen and phosphorus removal from slightly polluted water. Graphical abstract: Image 1 Highlights: A novel biofilm carrier integrating Fe–C micro-electrolysis with LDO was developed. A biofilter packed with Fe–C/LDO carrier removed N and P simultaneously. A large number of autotrophic denitrifying bacteria were enriched in the biofilm. Functional genes related to nitrogen metabolism and carbon cycle were analyzed.